(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
Abstract: Overtime, scholars have come up with diverse opinion regarding the impact of foreign direct investment (FDI) on economic growth in host communities. Similarly, empirical findings arising from different contexts and time have equally been contradictory. Current effort to resolve these inconsistency narrows down to sectoral concentration of multinational firms and the capacity of host communities to absorb foreign technology. In addition to these factors, this study deemed it necessary to highlight the importance of government regulatory role. Analysis that defined this investigation was founded on the Solow’s labour-augmented production function, while Autoregressive Distributed Lag (ARDL) bound test approach was employed in the estimation that followed using data for the period 1991 - 2022. The analysis produced interesting findings: First, results show that FDI has a significant negative impact on the growth of the manufacturing sector. Second, the importance of absorptive capacity and government regulatory quality in determining the nature and magnitude of impact of FDI in the growth of the manufacturing sector were equally evident.